2013
DOI: 10.1104/pp.113.228262
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Angle X-Ray Scattering and Solid-State Nuclear Magnetic Resonance Data Combined to Test Models for Cellulose Microfibrils in Mung Bean Cell Walls

Abstract: A synchrotron wide-angle x-ray scattering study of mung bean (Vigna radiata) primary cell walls was combined with published solid-state nuclear magnetic resonance data to test models for packing of (1→4)-b-glucan chains in cellulose microfibrils. Computersimulated peak shapes, calculated for 36-chain microfibrils with perfect order or uncorrelated disorder, were sharper than those in the experimental diffractogram. Introducing correlated disorder into the models broaden the simulated peaks but only when the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
183
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(199 citation statements)
references
References 47 publications
14
183
2
Order By: Relevance
“…Recent studies of cellulose structure have estimated 18 to 24 glucan chains per microfibril (Fernandes et al, 2011;Newman et al, 2013), contrary to the more widely accepted value of a 36 mer of glucan chains comprising a microfibril (Herth, 1983;Delmer, 1999;Doblin et al, 2002). As a consequence, the stoichiometry of the cellulose synthase complex has been revisited, and there is speculation that the individual particles of the hexameric rosette, identified in TEM studies, could contain as few as three CESA proteins (Newman et al, 2013;Hill et al, 2014).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Recent studies of cellulose structure have estimated 18 to 24 glucan chains per microfibril (Fernandes et al, 2011;Newman et al, 2013), contrary to the more widely accepted value of a 36 mer of glucan chains comprising a microfibril (Herth, 1983;Delmer, 1999;Doblin et al, 2002). As a consequence, the stoichiometry of the cellulose synthase complex has been revisited, and there is speculation that the individual particles of the hexameric rosette, identified in TEM studies, could contain as few as three CESA proteins (Newman et al, 2013;Hill et al, 2014).…”
Section: Resultsmentioning
confidence: 80%
“…Further, it has been recently reported that the stoichiometry of CESAs 1, 3, and 6 and CESAs 4, 7, and 8 in the primary and secondary cell walls, respectively, is 1:1:1 (Gonneau et al, 2014;Hill et al, 2014). Together, these reports suggest a rosette CSC composed of 18 CESA proteins with three CESAs per lobe as the most likely composition of a rosette CSC to account for an 18-chain cellulose microfibril (Newman et al, 2013;Gonneau et al, 2014;Hill et al, 2014). In addition, it should also be noted that 24 CESA proteins in a rosette CSC with four proteins per lobe is incompatible with a 1:1:1 CESA stoichiometry.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Cellulose is an unbranched homopolymer of >500 β-(1,4)-linked glucose units. In plant cell walls, cellulose is primarily in the form of crystalline microfibrils consisting of approximately 36 hydrogen-bonded cellulose chains, but also has amorphous regions (Somerville, 2006;Newman et al, 2013).…”
Section: Biomass Composition and Chemical Structuresmentioning
confidence: 99%